2022
DOI: 10.17533/udea.rccp.v35n3a02
|View full text |Cite
|
Sign up to set email alerts
|

Use of oral fluids for efficient monitoring of influenza viruses in swine herds in Colombia

Abstract: This unedited manuscript has been accepted by RCCP for future publication and is provisionally published on our website. The manuscript will undergo copyediting, typesetting, and galley review before final publication. Please note that this advance version may differ from the final version. Use of oral fluids for efficient monitoring of influenza viruses in swine herds in Colombia Uso de fluidos orales para el monitoreo eficiente de virus Influenza en granjas porcinas en Colombia Uso de fluidos orais para moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The phylogenetic analysis of the Colombian viruses confirmed what has been previously proposed about the genetic and antigenic dominance of the pandemic clade over classical FLUAV in the country since 2008 with no indication of the introduction of new H1 lineages or phylogenetic clades [26][27][28][29]. Nevertheless, the results presented here also provide evidence of the maintenance of the classical virus in Colombian pigs until 2021.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The phylogenetic analysis of the Colombian viruses confirmed what has been previously proposed about the genetic and antigenic dominance of the pandemic clade over classical FLUAV in the country since 2008 with no indication of the introduction of new H1 lineages or phylogenetic clades [26][27][28][29]. Nevertheless, the results presented here also provide evidence of the maintenance of the classical virus in Colombian pigs until 2021.…”
Section: Discussionsupporting
confidence: 87%
“…Epidemiological studies based on serology indicated that both H1N1 and H3N2 have been circulating among pig herds for at least 50 years [ 25 ]. More recently, research studies led to the isolation, sequencing, and partial genetic characterization of H1N1 strains in the country [ 26 , 27 , 28 , 29 ]. Regarding the H3N2 subtype, neither molecular evidence nor sequence data have yet been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The analyses of the first viral isolates in the country confirmed the presence of classic H1N1 from clade 1A in Antioquia in 2008 (34), as well as the introduction and dissemination of H1N1pdm09 to other major pig-producing regions since 2009 (33,37). Subsequent investigations validate the constant circulation of IAV, specifically H1N1pdm09 in Antioquia, Cundinamarca, Valle del Cauca, Meta, and the "Coffee Region" (formed by Caldas, Huila, Quindío, and Risaralda regions) (32,38,39). However, the change in IAV viral dynamics in the Colombian swine population after the introduction of H1N1pdm09 remains unclear.…”
Section: Introductionmentioning
confidence: 72%
“…Thus, more cost-efficient and convenient sampling methods with comparable sensitivity have been sought during the last decade. The groupbased approach of oral fluid sampling has become very popular because it is less time-consuming and does not require restriction of individual pigs, hence, it is considered a cost-effective and animal friendly diagnostic tool for swIAV detection [34][35][36][37][38][39]. However, although the diagnostic sensitivity of oral fluids for qualitative swIAV detection was comparable and the duration of viral RNA shedding was longer in group-based oral fluids compared to individual nasal swabs, the difficulty to isolate swIAV from oral fluids displayed a major drawback for surveillance purposes related to strain characterization [34,37,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%